Development of compact Compton camera for 3D image reconstruction of radioactive contamination. (6th November 2017) - Sato, Y.; Terasaka, Y.; Ozawa, S.; Miyamura, H. Nakamura; Kaburagi, M.; Tanifuji, Y.; Kawabata, K.; Torii, T.
Abstract: The Fukushima Daiichi Nuclear Power Station (FDNPS), operated by Tokyo Electric Power Company Holdings, Inc., went into meltdown after the large tsunami caused by the Great East Japan Earthquake of March 11, 2011. Very large amounts of radionuclides were released from the damaged plant. Radiation distribution measurements inside FDNPS buildings are indispensable to execute decommissioning tasks in the reactor buildings. We have developed a compact Compton camera to measure the distribution of radioactive contamination inside the FDNPS buildings three-dimensionally (3D). The total weight of the Compton camera is lower than 1.0 kg. The gamma-ray sensor of the Compton camera employs Ce-doped GAGG (Gd 3 Al 2 Ga 3 O 12 ) scintillators coupled with a multi-pixel photon counter. Angular correction of the detection efficiency of the Compton camera was conducted. Moreover, we developed a 3D back-projection method using the multi-angle data measured with the Compton camera. We successfully observed 3D radiation images resulting from the two 137 Cs radioactive sources, and the image of the 9.2 MBq source appeared stronger than that of the 2.7 MBq source.